Analisis Literatur Kebijakan Pariwisata Berkelanjutan di Kawasan Ekonomi Khusus Tanjung Lesung - Silla Anantasya Choirul Nisa; Taufiqurrohman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study expects to assess supportable the travel industry arrangements in the Tanjung Lesung Exceptional Financial Zone (SEZ). A literature review is the approach that is taken, and it involves gathering, analyzing, and combining data from various relevant literature sources. The outcomes demonstrate that economical the travel industry approaches in the Tanjung Lesung SEZ center around foundation improvement, natural safeguarding, and nearby local area strengthening. However, there are still some obstacles, such as a lack of infrastructure to support the project, inadequate community involvement, and issues with stakeholders' coordination. In conclusion, further efforts to improve infrastructure, the quality of facilities, community participation, and stakeholder coordination are required to achieve sustainable tourism goals in the Tanjung Lesung SEZ.This study expects to assess supportable the travel industry arrangements in the Tanjung Lesung Exceptional Financial Zone (SEZ). A literature review is the approach that is taken, and it involves gathering, analyzing, and combining data from various relevant literature sources. The outcomes demonstrate that economical the travel industry approaches in the Tanjung Lesung SEZ center around foundation improvement, natural safeguarding, and nearby local area strengthening. However, there are still some obstacles, such as a lack of infrastructure to support the project, inadequate community involvement, and issues with stakeholders' coordination. In conclusion, further efforts to improve infrastructure, the quality of facilities, community participation, and stakeholder coordination are required to achieve sustainable tourism goals in the Tanjung Lesung SEZ.